Breast Cancer: Epidemiology, Risk Factors and Survival Analysis in the Pakistani Population - Shumaila Zaib; Nosheen Masood; Jahangeer Sarwar Khan; Iqra; Azra Yasmin (University of Lahore, 2024)
Objective: To find out the association of genetic, reproductive and socio demographic factors with breast cancer in Pakistani women along with the sur- vival percentage of patients having breast cancer. Methodology: A case control study was carried out for a period of 3 years. Data were collected from different hospitals in Pakistan and the survival rate was determined by having direct contact with patients through telephone calls. For the estimation of survival probability Kaplan-Meier curve was used. Association of various demographic and epidemiological factors with breast cancer occurrence was estimated by using the odds ratio (OR) and 95% confidence interval (CI). Various tests used to find out the significance of results included student t-test, chi-square test, Fisher exact test and ANOVA. A statistical tool SPSS version 22 was used to analyze the data and results orientation. Results: The mean age for breast cancer diagnosis 47.3±11.8 years of age was found as mean age for breast cancer diagnosis. Higher BMI was the major contributing factors in developing breast cancer (OR=3.5, 95% CI=2.6-4.5). Significant risk factors found to be associated with the breast cancer included long reproductive period (menarche to menopause), family history of disease and habit of passive smoking (P<0.05). Out of 448 married patients, 23% were nulliparous and 26% of patients did not have a lactation history. Chemotherapy along with radiotherapy and surgery have been found to be effective methods for breast cancer treatment (80% survival). Conclusion: Present study concluded that age, body mass index, oral contraceptives usage, lactation duration, reproductive duration and marital status of the female are significant factors in developing breast cancer in Pakistani women. Keywords: Breast Cancer, Nulliparous, Chemotherapy, Radiotherapy.